Dotawo: A Journal of Nubian Studies 6: Miscellanea Nubiana (Punctum Books, 2019)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. Bringing together a collection of articles that were first presented as papers at the International Medieval Congress at the University of Leeds in 2016 and additional articles, the sixth volume of Dotawo showcases a diverse richness of topics concerning Nubia. The articles within this volume attest to the cultural, linguistic, geographic, and demographic diversity witnessed throughout Nubian history nationally and internationally amongst its neighbours, both near and far.